2023
DOI: 10.1038/s41598-023-36603-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polystyrene nanoparticles leads to changes in the zeta potential of bacterial cells

Abstract: Polymer molecules, the main components of plastics, are an emerging pollutants in various environmental compartments (water, air, soil) that may induce several ecotoxicological effects on live organisms. Therefore, understanding how plastic particles interact with bacterial cell membranes is crucial in analysing their associated risks in ecosystems and human microbiota. However, relatively little is known about the interaction between nanoplastics and bacteria. The present work focuses on Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…The synthesized AgNPs' stability was evaluated using zeta potential measurements, with a higher positive or negative value suggesting greater nanoparticle stability [ 93 ]. The distribution of size, both by intensity and mass, is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized AgNPs' stability was evaluated using zeta potential measurements, with a higher positive or negative value suggesting greater nanoparticle stability [ 93 ]. The distribution of size, both by intensity and mass, is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 c, indicative of high stability. Prior studies suggest that a strong negative zeta potential enhances repulsion between nanoparticles, promoting their stable dispersion and contributing to their colloidal quality [ 93 ]. Furthermore, the stability of AgNPs influences their size, with reduced stability leading to particle aggregation and an increase in particle size [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…30 As eDNA and pel possess a polyanionic nature, in the case of polystyrene NPs that are coated with positive and negatively charged molecules, electrostatic interactions can play a primary role 39 but not the only role in governing interactions between NPs and the P. aeruginosa matrix. Zając et al 40 demonstrated in biofilms, that the interactions of polystyrene NPs with the cell membranes of Staphylococcus aureus and Klebsiella pneumoniae led to changes in the zeta-potential of the bacterial cells, without causing cell death, and outcomes were dependent on particle concentration, pH, and exposure time. Additionally, studies have showed that kinetics of the interactions between biofilm components and functionalized nanoparticles were influenced by hydrophobic forces, van der Waals forces, pH, and steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that a combination of other additional properties such as surface charges might account for these responses. Owing to their elevated surface-to-volume ratio, the surface charges of microplastics have been reported to play a crucial role in influencing their functions and interactions within biological systems, potentially resulting in adverse effects [ 48 ]. Zeta potential measurements provide information about particle charges and dispersion stability, with absolute values above 30 mV indicating low aggregation that leads to good homogenization following exposure [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%